2007
DOI: 10.1007/s00125-007-0853-3
|View full text |Cite
|
Sign up to set email alerts
|

Metal-activated C-peptide facilitates glucose clearance and the release of a nitric oxide stimulus via the GLUT1 transporter

Abstract: When complexed to Fe2+ or Cr3+, C-peptide has the ability to promote ATP release from erythrocytes. This release is due to an increase in glucose transport through GLUT1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 25 publications
2
82
0
Order By: Relevance
“…Previous work from our laboratory has demonstrated a protective effect of C-peptide on the vasculature in hyperglycaemic conditions by decreasing inflammatory damage and the activation of nuclear factor (NF)-κB [13,15]. More recently, a physiological role in glucose clearance and the release of ATP from erythrocytes of diabetic patients has been suggested [27]. C-peptide has also been shown to improve erythrocyte deformability in diabetic people [28].…”
Section: Discussionmentioning
confidence: 98%
“…Previous work from our laboratory has demonstrated a protective effect of C-peptide on the vasculature in hyperglycaemic conditions by decreasing inflammatory damage and the activation of nuclear factor (NF)-κB [13,15]. More recently, a physiological role in glucose clearance and the release of ATP from erythrocytes of diabetic patients has been suggested [27]. C-peptide has also been shown to improve erythrocyte deformability in diabetic people [28].…”
Section: Discussionmentioning
confidence: 98%
“…C-Peptide has been suggested to stimulate the uptake of glucose into erythrocytes, resulting in increased ATP release (28,29). However, glucose entry into the erythrocyte is not the rate-limiting step in ATP formation via glycolysis (48).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously suggested that C-peptide-mediated increases in glucose entry into erythrocytes result in increased ATP release (28,29). We determined that when the concentration of glucose is elevated threefold (16.5 mM, ϳ300 mg/dl), a level that can be found in humans with type 2 diabetes, erythrocytes from healthy humans, and humans with type 2 diabetes demonstrated no change in low O 2 -induced ATP release compared with that observed at a more physiological glucose concentration (5.5 mM, 100 mg/dl).…”
Section: Effect Of Acute Exposure To High Glucose In the Presence Of mentioning
confidence: 99%
“…Insulin-independent effects of Cpeptide and metal activation C-peptide has been shown by our group and other groups to interact with RBCs [15][16][17][18]. In the studies involving deformability [15][16], the RBC samples were incubated with C-peptide alone and, after an incubation period, improvements in deformability of the RBCs obtained from diabetic patients were measured.…”
Section: C-peptide Secretion From Pancreatic Beta-cellsmentioning
confidence: 99%